Advanced Courses of Mathematical Analysis V Proceedings of the Fifth International School; (edited by Juan Carlos Navarro Pascual and El Amn Kaidi); V International Course of Mathematical Analysis in Andalusia Universidad de Almera, Almera, Spain, 12 - 16 - ANISIU, V. (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
The courses of Mathematical Analysis in Andalusia started in 2002 at the University of Cadiz at the initiative of the late Professor Antonio Aizpuru. Their aim was to provide opportunities for different research groups in Andalusia working in various areas of Mathematical Analysis to share information about their research and to cooperate, and, at the same time, to introduce the young researchers to the most advanced research lines.